A survey regarding orthodontic treatment among contemporary college freshmen in China - Tianyi Wang; Haolin Li; Xi Fan; Yongwen Guo (BMC, 2022)
Abstract Background A growing number of Chinese residents are seeking orthodontic treatment. The aim of the study was to investigate rates of orthodontic publicity, orthodontic treatment history and related factors among college freshmen in China, to preliminarily understand the current situation of orthodontic publicity and treatment in China, especially after the 2020s. Methods Referred to previous studies, a self-designed online questionnaire of Chinese college freshmen was conducted. The questionnaire was divided into two parts, after collecting basic information, we investigated orthodontic publicity rate and orthodontic treatment history with starting age, relapse phenomenon, satisfaction score and willingness to re-treatment. Factors hindering first-time and second-time treatment were also collected. The statistical analysis was performed using the Chi-square test, t-test, Kruskal-Wallis test and logistic regression analysis. Results The response rate was 100% and 3308 responses were included. The male to female ratio was 1524:1784 with a mean age of 18.43 years (SD 0.91 years). Statistically significant of economic administrative regions, age, major and orthodontics engagement of relatives or friends were found on prevalence and rate of orthodontic treatment (P < 0.05). Average opinion on orthodontic treatment was "satisfied" and most claimed a phenomenon of relapse (slight relapse: 38.22%, obvious relapse: 23.12%), where age, major and orthodontics engagement of relatives or friends showed statistically significant. Retreatment willingness was correlation with start age and relapse phenomenon. For those who refused first-time treatment, except for good tooth arrangement condition, pain, long-time span, and cost weighted, while for those who refused re-treatment, the fair of discomfort and long-time span ranked at the top. Conclusions In contemporary China, the prevalence and rate of orthodontic treatment had been greatly promoted. Earlier age for receiving orthodontic treatment was also discovered. Subjective factors regarding psychology, self-requirement affected the need of orthodontic treatment. Contemporary Chinese college freshmen had a high ability of judging dental alignment, while improve of overall orthodontic care level is still required.